2017
DOI: 10.1177/0956797617721271
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and Effortful Control in Toddlerhood Predict Academic Achievement Over a Decade Later

Abstract: A child's attachment to his or her caregiver is central to the child's development. However, current understanding of subtle, indirect, and complex long-term influences of attachment on various areas of functioning remains incomplete. Research has shown that (a) parent-child attachment influences the development of effortful control and that (b) effortful control influences academic success. The entire developmental cascade among these three constructs over many years, however, has rarely been examined. This a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 40 publications
1
13
0
1
Order By: Relevance
“…In preschoolers, a 12-week intervention designed to promote kindness was associated with better grades and well-being at the end of the year (Flook et al, 2015). A longer study linked socioemotional skills (but not happiness) at age 3 to educational achievement at age 15 (Dindo et al, 2017). A 3-year study of college students found associations between happiness and other markers of academic success like grades (Coffey et al, 2016).…”
Section: Why Are Happier Infants More Successful Adults?mentioning
confidence: 99%
See 1 more Smart Citation
“…In preschoolers, a 12-week intervention designed to promote kindness was associated with better grades and well-being at the end of the year (Flook et al, 2015). A longer study linked socioemotional skills (but not happiness) at age 3 to educational achievement at age 15 (Dindo et al, 2017). A 3-year study of college students found associations between happiness and other markers of academic success like grades (Coffey et al, 2016).…”
Section: Why Are Happier Infants More Successful Adults?mentioning
confidence: 99%
“…Happiness during infancy and childhood may be just as important as happiness during adulthood for initiating cascades of success and well-being (Coffey, 2018; Davis & Suveg, 2014). A primary marker of childhood success—education—is linked to earlier intellectual abilities, such as cognitive abilities and IQ (Abe & Izard, 1999; Ritchie & Tucker-Drob, 2018) and nonintellectual factors, such as emotions, emotion regulation, and relationship quality (e.g., Abe & Izard, 1999; Coffey, Wray-Lake, Mashek, & Branand, 2016; Dindo et al, 2017; Duyme, Dumaret, & Tomkiewicz, 1999; Davis & Suveg, 2014; Moffitt et al, 2011). As with happiness (Lyubomirsky, King, et al, 2005), intelligence and education are also linked to future success and well-being (Alloway & Alloway, 2010; Calvin et al, 2017; Lynn, 2010; Lynn & Mikk, 2009; Montez & Barnes, 2016; Ritchie & Tucker-Drob, 2018; Vaillant & Mukamal, 2001).…”
mentioning
confidence: 99%
“…The efficiency of executive attention is called “effortful control” 12,13 . Recent work 15 shows that the development of effortful control is influenced by parent-child attachment security. Combined with the findings of Peltola et al .…”
Section: Introductionmentioning
confidence: 99%
“…Del mismo modo, Mize y Pettit (1997) descubrieron que la alta sincronía madre-hijo estaba relacionada con las calificaciones de los maestros de preescolar respecto al funcionamiento social positivo del niño, es decir, con la atención, las habilidades para resolver problemas y con un menor uso de la agresión con sus pares. Dindo et al (2017) encontraron que prácticas de crianzas sincrónicas, caracterizadas por alta afectividad, interacción y seguridad durante la infancia predice el rendimiento académico durante la adolescencia. Muy especialmente, la sincronía materna se ha relacionado con la disposición a la obediencia infantil (Vite et al, 2010), con la reducción del estrés materno e infantil (Tarullo, John, & Meyer, 2017), y con el incremento en la frecuencia de conducta prosocial infantil (Ferreira et al, 2016), y estas variables tienen implicaciones importantes en el rendimiento académico (Rogers, Wiener, Marton, & Tannock, 2009).…”
Section: Introductionunclassified